The development of functional opsonophagocytic assays to evaluate antibody responses to Klebsiella pneumoniae capsular antigens - Robert Lawrence; Emma Bownes; Marina Johnson; Heather Fox; Drew Huff; Ivan Olave; Anup Datta; David Goldblatt; Nathalie Karaky (mSphere)
ABSTRACT Klebsiella pneumoniae is one of the leading causes of nosocomial infections in low- and middle-income countries (LMICs), with a high mortality rate among the immunocompromised. With increasing antibiotic resistance, there is an urgent need for preventive measures such as vaccines, but none are currently licensed for use. In order to evaluate natural immunity and assess the immunogenicity of novel vaccines, we set out to develop functional assays that effectively measure the immune response of K. pneumoniae anti-capsular antibodies in vitro. Serotypes KL2, KL15, KL25, KL62, and KL102 were targeted as these are five of the most prevalent and invasive strains, particularly in LMIC settings, and are putative vaccine antigens. Opsonophagocytic killing assays (OPAs) for each serotype were developed and qualified. Serotype-specific IgG from vaccinated rabbit sera and human sera was used to demonstrate in vitro antibody and complement-mediated killing for all serotypes tested, whereas cross-reactivity between each serotype was minimal by competitive analyses. These assays act as a platform to allow further serological evaluation of natural immunity and the performance of K. pneumoniae vaccines. Understanding the function of vaccine-induced antibodies, as well as natural IgG induced by exposure to K. pneumoniae, will be crucial to determine correlates of protection and aid in the path to licensure of a K. pneumoniae vaccine.IMPORTANCEK. pneumoniae is a pathogen that causes serious infections such as pneumonia and sepsis globally. The increasing prevalence of antibiotic resistance in this pathogen has complicated treatment efforts, highlighting the need for preventive therapeutic strategies such as vaccination. However, no licensed vaccines are currently available. Standardized assays to assess the immunogenicity of new vaccines are crucial for vaccine development and evaluation of other therapeutics. Therefore, we have developed assays that can assess the functionality of antibodies, which can be used to evaluate the potential of novel K. pneumoniae conjugate vaccines, and inform which antibodies are most effective for preventing disease.